Facility Location Model for Emergency Humanitarian Logistics Using Set Covering and Analytic Network Process (ANP) Method - Prafajar Suksessanno Muttaqin; Rizki Afif Finata; Ami Ayu Masturo (Institut Teknologi Sepuluh Nopember, 2020)
This research will conduct set covering problem and analytical network process in determining the location of the swab test due to the outbreak of corona virus infection disease 2019 (Covid-19) in Bandung. The location of the swab test can also function as a location for fulfilling medical aids to the residents around the affected area. Solving the solution is done by developing a mathematical model consisting of numbers 1 and 0 in the form of integer linear programming with an output that is zero-one. The objective function is to minimize number of swab test location. From the results, it was found that the location of the swab test was chosen so that it could fulfill the affected areas in Bandung City. Furthermore, using the analytical network process approach, it is obtained 5 criteria, which are then weighted for each criterion, so the calculation results show that area Cicendo is a priority for the location of swab test.